A A CASE OF CENTRAL NERVOUS SYSTEM INVASIVE ASPERGILLOSIS MIMICKING ORBITAL CELLULITIS IN A PATIENT WITH UNCONTROLLED TYPE 2 DIABETES MELLITUS AND END-STAGE RENAL DISEASE - Sardar, Zomer; Nasim, Azhar; Mohammad Faisal,; Danish Iqbal, Mariam (Journal of Ayub Medical College Abbottabad, 2026)
Central nervous system aspergillosis is a rare and often fatal complication seen in immunocompromised individuals. Here, we present the case of a 60-year-old female with uncontrolled type 2 diabetes mellitus and end-stage renal disease (ESRD) who was ultimately diagnosed with CNS aspergillosis. This case underscores the diagnostic challenge and delays posed by fungal infections in patients with predisposing conditions, necessitating a multidisciplinary approach for timely diagnosis and management.